Alcohol and Suicide: Neurobiological and Clinical Aspects - Leo Sher (The Scientific World Journal)
Alcohol, primarily in the form of ethyl alcohol (ethanol), has occupied an important place in the history of humankind for at least 8,000 years. In most Western societies, at least 90% of people consume alcohol at some time during their lives, and 30% or more of drinkers develop alcohol-related problems. Severe alcohol-related life impairment, alcohol dependence (alcoholism), is observed at some time during their lives in about 10% of men and 3—5% of women. An additional 5—10% of each sex develops persistent, but less intense, problems that are diagnosed as alcohol abuse. It this review, neurobiological aspects of suicidal behavior in alcoholism is discussed. In individuals with comorbid depression and alcoholism, greater serotonergic impairment may be associated with higher risk of completed suicide. Dopaminergic dysfunction may play an important role in the pathophysiology of suicidal behavior in alcoholism. Brain damage and neurobehavioral deficits are associated with alcohol use disorders and may contribute to suicidal behavior in persons with alcohol dependence or abuse. Aggression/impulsivity and alcoholism severity affect risk for suicide among individuals with alcoholism. Major depressive episodes and stressful life events particularly, partner-relationship disruptions, may precipitate suicidal behavior in individuals with alcohol use disorders. Alcohol misuse and psychosocial adversity can combine to increase stress on the person, and, thereby, potentially, increase the risk for suicidal behavior. The management of suicidal patients with alcohol use disorders is also discussed. It is to be hoped that the efforts of clinicians will reduce morbidity and mortality associated with alcohol misuse.